PENAMBAHAN ABU JERAMI DAN ABU SEKAM PADI PADA CAMPURAN BATU BATA UNTUK MENINGKATKAN KUALITAS DAN EFISIENSI PRODUKSI BATU BATA INDUSTRI TRADISIONAL - Anis Rahmawati; Ida Nugroho Saputro (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
The purpose of this study was to determine the effect of rice husk ash and ash rice straw against physical and mechanical characteristics of the bricks, and also to determine the minimal burning time in the manufacture of clay bricks with additional ingredients such waste to achieve physical and mechanical characteristics bricks in accordance with standard bricks. Variations of burning time is 12 hours, 18 hours, 24 hours, and 30 hours. While the variation of rice husk ash and rice straw ash is 0%, 5%, 10%, 15% and 20%. The bricks were tested based on physical and mechanical characteristics. Physical characteristics include specific gravity test, fuel and shrinkage porosity test. While the mechanical characteristics are compressive strength test.Based on these results, it was found that all the bricks compressive strength test in accordance with ISO standards SK-S-04-1989-F, which is entering grade 25 and 50. The density is smaller than the standard that is 1.8 to 2.6 g / cm3. Test shrinkage derived fuel is smaller than the standard that is 15%. While the porosity test found to be greater than the standard (20%). The highest compression strength is 7.35 MPa is achieved with brick with an additional 20% ash burning rice straw in 12 hours. Its low specific gravity of 1.32 g / cm3, achieved by brick with the addition of 20% rice husk ash on burning 30 hours. Losses lowest fuel that is 0.90% achieved by brick with the addition of 20% rice husk ash on burning 12 hours. While the lowest was 33.17% porosity is achieved by brick with the addition of 10% rice husk ash on burning 24 hours.